2016
DOI: 10.4168/aair.2015.8.1.79
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Atopic Dermatitis in Korean Children Based on Data From the 2008-2011 Korean National Health and Nutrition Examination Survey

Abstract: This is an Open Access article distributed under the terms of the Creative Commons Attribution Non-Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted non-commercial use, distribution, and reproduction in any medium, provided the original work is properly cited.Population-based studies of atopic dermatitis (AD) in Korean children are lacking. Thus, the purpose of this study was to determine the prevalence, geographic distribution, and risk factors of AD in the Korean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 32 publications
2
6
1
Order By: Relevance
“…Our results indicate that adults with lower income are more likely to currently suffer from atopic dermatitis. This differs from previous research indicating that people with higher socioeconomic status are more likely to suffer from atopic dermatitis (Kim et al, 2015;Lee, Han, Kim, Park, & Park, 2016;Peters et al, 2010). The difference might be attributable to the fact that we focused on individuals who were currently suffering from the disease among those with an actual diagnosis.…”
Section: Associations Between Currently Suffering From Atopic Dermacontrasting
confidence: 77%
“…Our results indicate that adults with lower income are more likely to currently suffer from atopic dermatitis. This differs from previous research indicating that people with higher socioeconomic status are more likely to suffer from atopic dermatitis (Kim et al, 2015;Lee, Han, Kim, Park, & Park, 2016;Peters et al, 2010). The difference might be attributable to the fact that we focused on individuals who were currently suffering from the disease among those with an actual diagnosis.…”
Section: Associations Between Currently Suffering From Atopic Dermacontrasting
confidence: 77%
“…The prevalence of AD has been increasing in recent decades, [1][2][3] and the incidence of physician-diagnosed AD has also risen in Korea. 4,5 While the underlying mechanisms in pathogenesis of AD are not fully understood, it is generally accepted that the interplay of individual genetic predisposition and environmental factors contribute to the development of AD. The reason for the increasing prevalence of AD of Korea is unclear but might be due to environmental change; it is widely believed that the Westernized lifestyle that has resulted from industrialization, which includes increased levels of air pollution, 6 enhanced hygiene 7 and reduction in the incidence of infections early in life, has contributed to increasing prevalence of AD.…”
Section: Introductionmentioning
confidence: 99%
“…Atopic dermatitis (AD) is a chronic and relapsing inflammatory disease. Recent epidemiological studies have reported an abrupt increase in the incidence and prevalence of AD over the past few decades 1,2 . A concomitant increase of AD and other atopic disorders such as asthma and allergic rhinitis has led to epidemiological research and suggested that the widespread use of antibiotics during early childhood is associated with the abrupt increase in the prevalence of atopic disorders 3–6 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent epidemiological studies have reported an abrupt increase in the incidence and prevalence of AD over the past few decades. 1,2 A concomitant increase of AD and other atopic disorders such as asthma and allergic rhinitis has led to epidemiological research and suggested that the widespread use of antibiotics during early childhood is associated with the abrupt increase in the prevalence of atopic disorders. [3][4][5][6] This association can be explained by the "microflora hypothesis", that a perturbation in the gastrointestinal microbiota induced by antibiotics can cause immune dysregulation, leading to atopic disorders.…”
Section: Introductionmentioning
confidence: 99%